Seismic performance analysis of self-centering segment piers with mortise-tenon shear connectors based on cyclic pseudo-static test - Yongjun Ni (JVE International, 2021)
In the past decades, more and more precast piers have been used in actual engineering, which brings convenience in construction and standardization of production. However, precast piers still have some shortcomings, such as shear slip between segments and poor energy dissipation. Thus, a self-centering mortise-tenon segmental bridge pier was proposed in this paper. To research the seismic performance of the self-centering mortise-tenon segment piers, three scaled model piers with their scale ratio as 1:3 were designed and prefabricated, namely as a cast-in-place model pier (CP) and 2 self-centering mortise-tenon segment model piers (designated as MTSP1 and MTSP2) with the initial pretension of 1302 MPa and 1488 MPa, respectively. The cyclic pseudo-static tests of the three piers were carried out. The comparison analysis was made respecting to the test results including the damage form, hysteretic characteristics, skeleton curve, energy dissipation capacity, residual displacement and equivalent stiffness of the three specimens. It was shown that MTSP specimens had higher horizontal bearing capacity. While the yield load, ultimate load, displacement ductility coefficient and initial stiffness of MTSP1 and MTSP2 were higher than those of CP. The MTSP had better performance considering the above aspects. The mean value of the residual displacement of MTSP2 was lower than that of CP 21.14 % and 29. 72 % respectively, as the drift ratio reaching 5 %. The MTSP specimens had better self-centering capacity due to the increased pretension stress which reducing the residual displacement greatly. The energy dissipation reinforcements improved the energy dissipation capacity of the segmental assembled piers. Based on the ABAQUS model, the numerical simulation was carried out and compared with the experimental data. MTSP had great energy dissipation capacity and self-centering capacity. It was suggested that MTSP should be used to make up for the deficiency of segmental assembled pier and improve the seismic performance of segmental assembled pier.